Response of induction motor to balance voltage sags and momentary interruption - Surya, Hardi; Ismail, Daut, Prof. Dr.; Che Mat, Hadzer; Risnidar, Chan, Ir.; Muhammad Irwanto; Pungut, Ibrahim (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.